PERSEPSI KONSUMEN TERHADAP MAKANAN ORGANIK DI YOGYAKARTA - Danang Waskito; M Ananto; Andre Reza (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractThe aim of this research is to reveal the perception of the consumers in Yogyakartatowards organic food. This research used a quantitative descriptive methodwith 118 respondents using a judgemental sampling technique. The consumers’perception toward organic food is referred to the perception toward health, quality,price, and food safety. The findings show that consumers in Yogyakarta have a highperception of organic food which is good for health as it has higher nutrition, can keepand increase the body imune.